1999
DOI: 10.1038/sj.onc.1202988
|View full text |Cite
|
Sign up to set email alerts
|

Mouse ULK2, a novel member of the UNC-51-like protein kinases: unique features of functional domains

Abstract: The UNC-51 serine/threonine kinase of C. elegans plays an essential role in axonal elongation, and unc-51 mutants exhibit uncoordinated movements. We have previously identi®ed mouse and human cDNAs encoding UNC-51-like kinase (ULK1). Here we report the identi®cation and characterization of the second murine member of this kinase family, ULK2. Mouse ULK2 cDNA encodes a putative polypeptide of 1033 aa which has an overall 52% and 33% amino acid identity to ULK1 and UNC-51, respectively. ULKs and UNC-51 share a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 27 publications
2
106
0
Order By: Relevance
“…Unlike the previously described model systems, vertebrates contain two genes, ULK1 and ULK2, that encode proteins with close homology to Atg1p. Both ULK1 and ULK2 are widely expressed in mouse tissues and kinase-dead versions of ULK1 and ULK2 can act as dominant negative proteins in neurite outgrowth assays (34,38). We found that knockdown of ULK2 did not inhibit GFP-LC3 conversion, suggesting that only ULK1 has autophagy regulatory roles, at least in 293 cells.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Unlike the previously described model systems, vertebrates contain two genes, ULK1 and ULK2, that encode proteins with close homology to Atg1p. Both ULK1 and ULK2 are widely expressed in mouse tissues and kinase-dead versions of ULK1 and ULK2 can act as dominant negative proteins in neurite outgrowth assays (34,38). We found that knockdown of ULK2 did not inhibit GFP-LC3 conversion, suggesting that only ULK1 has autophagy regulatory roles, at least in 293 cells.…”
Section: Discussionmentioning
confidence: 74%
“…Studies performed using Dictyostelium, Drosophila, and C. elegans have confirmed a role for their Atg1 homologs in autophagy (6,7,31,32). In mammals, two Atg1 homologs have been identified, uncoordinated 51-like kinase 1 (ULK1) and ULK2 (33,34), and we recently demonstrated an involvement of ULK1 in the subcellular re-distribution of mammalian Atg9 that takes place following nutrient starvation (35). Evidence from Drosophila and mammalian cells also indicate that Atg1 proteins have the ability to signal "upstream" to TOR via a feedback loop (32,36).…”
mentioning
confidence: 96%
“…2 Atg1 homologues have been reported in several species, including mammals, where there are two Atg1 homologues, UNC (uncoordinated movement)-51-like kinase 1 (ULK1) and ULK2. 76,77 Tooze and coworkers 78 have shown that siRNA-mediated knockdown of ULK1, but not ULK2, inhibited rapamycin-induced autophagy, further suggesting a role downstream of mTOR. This is consistent with our earlier finding in which rapamycin failed to rescue neurodegeneration in Drosophila with heterozygous loss of Atg1.…”
Section: Downstream Targets Of Mtor and Mtor-independent Regulatorsmentioning
confidence: 99%
“…9,14 The autophagy process and many of the autophagy-specific proteins are conserved in higher eukaryotes. Unc-51 like kinase 1 (ULK1) and unc-51 like kinase 2 (ULK2) have sequence homology to Atg1, [15][16][17] but only recently was ULK1 confirmed to have a functional role in autophagy. Three different studies have used siRNA to deplete cells of ULK1, demonstrating that ULK1 is important for the starvation-induced trafficking of mAtg9, for lipid modification of GFP-LC3, and for the macroautophagymediated degradation of a cytosolic protein.…”
Section: Introductionmentioning
confidence: 99%